(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to identify the challenges of generative artificial intelligence in developing multimedia-based learning environments, as researchers saw that generative artificial intelligence tools for multimedia have spread rapidly in the last three years, through which simple text processors can generate digital objects in the form of video, images and animations. Since educational environments are almost devoid of multimedia, it is important to examine the challenges that generative intelligence tools can present to multimedia-based educational environments. Since the use of multimedia is primarily based on the principles of the cognitive theory of multimedia learning, reviewing the challenges associated with the use of generative intelligence tools will be linked to the principles of the cognitive theory of multimedia learning. The current research relied on the phenomenological approach in conducting a set of interviews with (6) experts specialized in the use of generative intelligence tools in the field of multimedia. According to the objective analysis processes, the most prominent results were that the challenges are based on educational challenges, organizational, legislative, technical and technological challenges.